“Ethical Minefields” and the Voice of Common Sense: A Discussion with Julian Savulescu - Savulescu, Julian; Protopapadakis, Evangelos D. (Conatus - Journal of Philosophy, 2019)
Theoretical ethics includes both metaethics (the meaning of moral terms) and normative ethics (ethical theories and principles). Practical ethics involves making decisions about every day real ethical problems, like decisions about euthanasia, what we should eat, climate change, treatment of animals, and how we should live. It utilizes ethical theories, like utilitarianism and Kantianism, and principles, but more broadly a process of reflective equilibrium and consistency to decide how to act and be.